Franck’s Right to Democratic Governance and the Role of Democratic Sanctions - Bernatskyi, Bohdan (Kyiv-Mohyla Law and Politics Journal, 2018)
In 1992, Tomas Franck conceptualized the democratic entitlement theory — a new approach regarding the international validation of governance, which was previously based solely on the “doctrine of effective control.” This led to the emergence of a new international norm under which only democracy can validate a government’s legitimacy. Twenty years later, the theory proposed by Franck has gained more currency. International organizations and states began and continue to address the legitimacy of a government by imposing democratic sanctions. This article proposes to corroborate the Franck democratic entitlement theory by incorporating democratic sanctions, while also consolidating cases where sanctions were applied, inter alia, construing legal status of such measures.